Evaluating the effects of road hump on traffic volume and noise level at Taman Keramat residential area, Kuala Lumpur - Rosli, Nur Shazwani; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies, 2013)
This paper investigates the effects of road hump on traffic volume and noise level in a residential area in Kuala Lumpur. Field surveys were administered to measure data on traffic volume and noise level at three selected roads at Taman Keramat residential area in Kuala Lumpur. Measurement on noise levels such as LAeq, LAFmax and LAFmin and traffic volume were undertaken for about 12 hours. The findings show that the highest traffic volume (563 vehicles per hour)and the highest noise level (75dB(A))was measured at Road 1. The correlation analysis indicates a similar pattern in the relationship between traffic volume and noise level especially at Road 2 and Road 3. Finally, this paper concludes in drawing attention to conduct further studies on the effects of road humps in other residential areas in Kuala Lumpur to implement measures for a pleasant, harmonious and safe living environment for the community